ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI - Pratiwi, Nurmala Widia; Suseno, Y. Djoko; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This study aims to: (1) Analyze the significance of the influence of the work environment on the performance of BPPKAD Ponorogo Regency employees. (2) Analyze the significance of the influence of leadership style on the performance of BPPKAD Ponorogo Regency employees. (3) Analyze the significance of the influence of the work environment which is moderated by leadership style on the performance of BPPKAD Ponorogo Regency employees. The population and population used in this study were all employees of the Ponorogo Regency BPPKAD, amounting to 96 people. Data collection techniques using a questionnaire that has passed the test of validity and reliability. The regression requirements test uses the classic assumption test. The data analysis technique uses multiple linear regression analysis with absolute difference test and hypothesis testing is done through t test. The results of this study indicate that: 1) The work environment has a significant effect on the performance of BPPKAD Ponorogo Regency employees. So the hypothesis that states is significant. 2) The leadership style has a significant effect on the performance of BPPKAD Ponorogo Regency employees. So the hypothesis that states is significant. 3) Leadership style is not able / not proven to moderate the influence of the work environment on the performance of BPPKAD Ponorogo Regency employees.